Psychological Dimensions of Retirement - Alpass, Fiona; Paddison, Johanna; Flett, Ross; Wright, Sarah; Pachana, Nancy; Biggs, Herbert; Pennington, Helen; Neville, Stephen (Massey University, 2013)
The chapters that follow examine the character of, and issues relating to, western retirement experiences. As our populations age, issues relating to the nature of retirement are of growing importance. Population ageing is a global issue. For instance, Jacobsen, Kent, Lee, & Mather (2011) report that currently one-fifth of the Japanese population is aged over 65 and estimated to increase to one-third of the population by 2040. Based on Bogomolny’s (2004) calculations, by 2025, there will 2 workers in Japan for every person over 65. By 2030 to 2040, 20% of the United States population (i.e., 70 million people), will be aged over 65 (Conrad Glass & Flynn, 2000; Jacobsen, Kent, Lee & Mather, 2011). A drop in the number of workers per government funded beneficiaries from 3.3. to 2.2 has also been predicted (Social Security Board of Trustees, 2008). Many European countries will have similarly high proportions of their population aged over 65 (Heyma, 2004) with concomitant dependency ratios, as will Australia and New Zealand (Kippen, 2002; Statistics New Zealand, 2012). In the 1970s and 1980s there was a trend toward early retirement, however this began to be reversed in many countries in the 1990s. Participation rates in most OECD countries for older workers (50-64 years) have increased to an average of 63% in 2008. Some countries have seen considerable increases in participation rates for these workers (e.g. New Zealand, Netherlands) and in even older workers (65-69 years) (OECD, 2011). Along with the increasing expansion of working lives has come an evolution of the pathways to retirement. Retirement is no longer necessarily a “clean break” from the workforce, with many researchers arguing that the transition from work to retirement is now “blurred”. Retirement is not a single discrete event but can be viewed as an individual process, where for many paid employment still plays a significant role well into the “third age”. The changing nature of retirement over the past few decades highlights the need to continually reassess how we conceptualise it in the literature and how it impacts on the individual, organisations and society. This book seeks to address some of the psychological dimensions of retirement prominent in the literature. The initial chapter of this book outlines a number of definitions pertinent to the topic of retirement. This is followed by an examination of issues that affect retirement decisions. Next, psychological wellbeing and physical health issues are examined in relation to retirement. The final chapters examine the interplay between work and retirement, the role of leisure in retirement, the experiences of women, and the sources and role of social support in retirement.
Keywords: Retirement; Wellbeing; Ageing population